PEST AND DISEASE MONITORING WITH CONTROL MEASURES ON CHILI (Capsicum frutescens L.) PLANTATION IN TURI, SLEMAN, YOGYAKARTA: PEMANTAUAN HAMA DAN PENYAKIT SERTA TINDAKAN PENGENDALIANNYA PADA LAHAN CABAI (Capsicum frustescens L.) DI TURI, SLEMAN, YOGYAKARTA - Satria Wisnu Baja Palapa; Annisa Nur Hidayati; Naila Rahma Ulya; Muhammad Daffa Ardian (Agrofarm: Jurnal Agroteknologi, 2026)
Red chili (Capsicum annuum L.) is an important horticultural crop in Indonesia, but its productivity is often constrained by pests and diseases. Monitoring is carried out to identify pest and disease infestations, analyze attack patterns, and determine the factors influencing their distribution and intensity. This study aimed to identify the types of pests and diseases affecting chili plantations in Turi, Sleman, Yogyakarta, and to evaluate their incidence and intensity. The research was conducted in October 2025 using a diagonal sampling method at five observation points, with ten plants randomly selected per point. The results are expected to provide a basis for effective and sustainable pest and disease management to support chili productivity.